Reliability and power supply capability evaluation of active distribution networks with four‐terminal soft open points. Issue 5 (16th June 2020) - Yan, Feng; Chen, Xiangyan; Tang, Wensheng; Yan, Ri; Wu, Hao
Abstract : Soft open points (SOPs) have the ability to regulate the power flow among their terminals in a continuous manner, which can solve the problems brought by the synergy of distribution networks and distributed generation, and improve the system reliability and power supply capability. To address the current lack of quantitative measurement on the effects of SOPs, the power supply capability evaluation method for active distribution networks (ADNs) with four‐terminal SOPs considering reliability is proposed. Firstly, the topology and configuration modes of four‐terminal SOPs are studied, and their control modes are investigated in normal operation and supply restoration conditions. Then, using the feeder partition method, the effects of four‐terminal SOPs on the power outage duration of different load areas after a fault are studied, and the reliability evaluation process for ADNs with four‐terminal SOPs is developed based on the quasi‐Monte Carlo method. Later, with reliability as the main constraint, the power supply capability evaluation model for ADNs with four‐terminal SOPs is established, and the solution algorithm is proposed. Finally, the effectiveness and applicability of the method proposed are verified through a case study.